1999
DOI: 10.1046/j.1432-1327.1999.00876.x
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular organization of photosystem II and its light‐harvesting antenna in partially solubilized photosystem II membranes

Abstract: We present an extended analysis of the organization of green plant photosystem II and its associated lightharvesting antenna using electron microscopy and image analysis. The analysis is based on a large dataset of 16 600 projections of negatively stained PSII±LHCII supercomplexes and megacomplexes prepared by means of three different pretreatments. In addition to our previous work on this system [Boekema, E.J., van Roon, H., Calkoen, F., Bassi, R. and Dekker, J.P. (1999) Biochemistry 38, 2233±2239], the follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
158
1
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 168 publications
(167 citation statements)
references
References 40 publications
7
158
1
1
Order By: Relevance
“…Imaging and image processing were performed as described in previous studies (Oostergetel et al, 1998;Boekema et al, 1999;Watanabe et al, 2014). For the final class sums, the best 10% of the projections were summed.…”
Section: Em Of Isolated Psi Oligomers and Ts-821 Thylakoidsmentioning
confidence: 99%
“…Imaging and image processing were performed as described in previous studies (Oostergetel et al, 1998;Boekema et al, 1999;Watanabe et al, 2014). For the final class sums, the best 10% of the projections were summed.…”
Section: Em Of Isolated Psi Oligomers and Ts-821 Thylakoidsmentioning
confidence: 99%
“…LHCII is the major component of the outer antenna and comprises different heterotrimers of LHCB1, LHCB2, and LHCB3 gene products, while minor antenna complexes (Chlorophyll Protein 29 [CP29], CP26, and CP24) are encoded by LHCB4, LHCB5, and LHCB6 genes, respectively, and are found as monomers (Bassi et al, 1996;Jansson, 1999). Structural analysis of PSII and Lhcb supercomplex organization within grana membranes has revealed that minor complexes CP26 and CP29 are located in between the core complex and the trimeric LHCII (Harrer et al, 1998;Boekema et al, 1999). Additional LHCII trimers, depending on growth light intensity (Dekker and Boekema, 2005;Morosinotto et al, 2006;Ballottari et al, 2007), complete the PSII structure and require CP24 for connection to PSII core by forming a complex with CP29 (Bassi and Dainese, 1992;Yakushevska et al, 2003;Dekker and Boekema, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In the stably bound S trimer, Lhcb1 and Lhcb2 are more abundant, whereas the moderately bound M trimer contains mostly Lhcb1 and Lhcb3 (Galka et al, 2012). PSII supercomplexes isolated from spinach (Spinacia oleracea) showed the presence of an extra LHCII trimer (L trimer); therefore, it is possible that, in Arabidopsis, other trimers are associated with the PSII dimer in a more labile supercomplex that cannot be isolated (Boekema et al, 1999). A single LHCII trimer, containing Lhcb1 and Lhcb2, stably associates with PSI to constitute the PSI-LHCII supercomplex, whose formation is dependent on LHCII phosphorylation by STN7 in state 2 (Kouril et al, 2005;Galka et al, 2012).…”
mentioning
confidence: 99%